The autocatalytic character of the growth of production knowledge: What role does human labor play? - Thomas Brenner; Christian Cordes (Max Planck Institute for Research into Economic Systems, 2004)
This paper analyzes how the qualitative change in human labor occurs in mutual dependence with the advancement of the epistemic base of technology. Historically, a recurrent pattern can be identified: humans learned to successively transfer labor qualities to machines. The subsequent release of parts of the workforce from performing this labor enabled them to spend this spare time in the search for further technical innovations, i.e., the generation and application of ever-more knowledge. A model examines the autocatalytic relationship between the production of commodities and knowledge. The driving forces of these processes and the mechanisms that limit them are analyzed.
Keywords: E23; J24; N30; O30; O40; 330; technological change; long-term economic development; production; productivity growth; labor market; Produktionstechnik; Technischer Fortschritt; Arbeit; Rationalisierung; Evolutionsökonomik; Theorie